2011
DOI: 10.1186/1471-2164-12-454
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of transcriptome dynamics during watermelon fruit development: sequencing, assembly, annotation and gene expression profiles

Abstract: BackgroundCultivated watermelon [Citrullus lanatus (Thunb.) Matsum. & Nakai var. lanatus] is an important agriculture crop world-wide. The fruit of watermelon undergoes distinct stages of development with dramatic changes in its size, color, sweetness, texture and aroma. In order to better understand the genetic and molecular basis of these changes and significantly expand the watermelon transcript catalog, we have selected four critical stages of watermelon fruit development and used Roche/454 next-generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
103
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 60 publications
15
103
0
Order By: Relevance
“…For example, only 17.85 % of the unigenes were annotated using the GO tool, and only 36.85 % were annotated in the Nr database. This is consistent with previous reports of 20-40 % annotation efficiency in eukaryotes (Meyer et al 2009;Wang et al 2010a, b), although lower than some studies (Guo et al 2011;Ji et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…For example, only 17.85 % of the unigenes were annotated using the GO tool, and only 36.85 % were annotated in the Nr database. This is consistent with previous reports of 20-40 % annotation efficiency in eukaryotes (Meyer et al 2009;Wang et al 2010a, b), although lower than some studies (Guo et al 2011;Ji et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…The rate of reads with Q20-value reached 98.68%. Based on these reads, 96,149 unigenes were assembled with an average length of 973 bp, which was larger than the mean unigene lengths found in butterfly (197 bp;Vera et al, 2008), sweet potato (581 bp; Guo et al, 2011), Salvia miltiorrhiza (331 bp; Zhang et al, 2012), safflower (446 bp; Lulin et al, 2012), and wax gourd (709 bp; Jiang et al, 2013). We aligned the unigene sequences to the Nr, Swiss-Prot, GO, COG, and KEGG protein databases and found that most unigene sequences could be matched to unique protein sequences in the various databases.…”
Section: Discussionmentioning
confidence: 97%
“…Paired-end Illumina libraries were prepared following the manufacturer's instructions and sequenced on an Illumina GAII system. We sequenced 44,75 or 90 bp at each end. The Illumina paired-end reads from each watermelon accession were aligned to the reference 97103 genome sequences using BWA 67 .…”
Section: Methodsmentioning
confidence: 99%
“…Fruit flesh and rind tissues of 97103 were collected at four developmental stages: 10, 18, 26 and 34 days after pollination 75 . RNA extraction and strand-specific RNA-Seq library preparations were performed as described 44 , and RNA-Seq libraries were sequenced on the Illumina HiSeq 2000 system.…”
Section: Methodsmentioning
confidence: 99%